Peningkatan Kemampuan Motorik Kasar Anak 5-6 Tahun Di PAUD Rerawete Melalui Penggunaan Alat Permainan Tradisional - Rendo, Maria Erosiana; Dhiu, Konstantinus Dua; Laksana, Dek Ngurah Laba; Ngura, Elisabeth Tantiana (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This research aims to increase the use of traditional play tools in developing the gross motor physical aspects of children aged 5-6 years in PAUD Rerawete. The research method used is class action research (PTK) with two cycles, each of which consists of planning, implementation, observation, and reflection stages. The subjects of this study are group B children at PAUD Rerawete. The results showed that after the application of modified traditional play tools, there was a significant improvement in children's gross motor skills, including balance, coordination, and muscle strength. In the first cycle, the average gross motor development of children reached 65%, while in the second cycle it increased to 85%. In addition, children show higher enthusiasm and participation in physical activities. In conclusion, the use of improved traditional play tools has proven to be effective in supporting the gross motor physical development of children aged 5-6 years at PAUD Rerawete. Therefore, it is recommended for educators to make better use of traditional games as a fun and beneficial learning strategy for children's development.